FAKTOR-FAKTOR YANG MEMPENGARUHI ADOPSI TEKNOLOGI INFUS ASAP DI KABUPATEN TIMOR TENGAH SELATAN, NTT- INDONESIA - Yasintha L. Kleden (Jurnal Kawistara, 2014)
The utilization of Smoke Infusion Technology in corn storage has traditionally been proven to reducethe damage of corn caused by the attack of Sitophilus zeamais up to 20%. However, no matter how gooda technollogy is invented, it will be useless without the adoption process by the farmers. The researchon the response of the farmers on smoke infusion technology in corn storage has been conducted fromAugust to October 2013 with the objective to reveal the factors affecting the response of the farmers onthat technology. This research was conducted on 2 sub-regencies in south timor tengah regency, as thetesting site of smoke infusion technology. The number of respondents as much as 100 sample farmers,including 50 farmers from Batu Putih sub-regency and 50 sample farmers from Oenino sub-regency.Variables used to estimate the response of the farmers on smoke infusion technology include: attitude,age, education, size of land,state of land owner,active farmers, risk, the role of agents of social reformersand social leader role. The data is analyzed through the methods of descriptive and multiple regresionanalysis. The result of the research shows that the farmers for adoption on TIA is more dominantlyinfluenced by attitude, age, risks and social leader role.